2017
DOI: 10.1016/j.jcf.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of posture on lung ventilation distribution and associations with structure in children with cystic fibrosis

Abstract: Body posture influences lung volumes and ventilation distribution in both healthy children and children with CF. MBW testing in the supine posture strengthened associations with structural lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
1
22
1
1
Order By: Relevance
“…The effect of posture on LCI in children with CF has recently been assessed [ 5 ]. This study compared CF children with mild disease to healthy controls (HC) and showed that LCI in the supine posture was elevated when compared to sitting and that supine LCI correlated better than sitting LCI with metrics derived from high resolution computed tomography (HRCT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of posture on LCI in children with CF has recently been assessed [ 5 ]. This study compared CF children with mild disease to healthy controls (HC) and showed that LCI in the supine posture was elevated when compared to sitting and that supine LCI correlated better than sitting LCI with metrics derived from high resolution computed tomography (HRCT).…”
Section: Introductionmentioning
confidence: 99%
“…Further to the work of Ramsey et al [ 5 ], the aim of this study therefore was to compare LCI and the phase III slope parameters S cond and S acin , sitting and supine, in children with a range of CF lung disease as well as in HC, and to measure the extent to which changing lung volume affects the change in LCI. We hypothesised that supine posture would firstly reduce lung volume (FRC) with a resultant effect on gas mixing, but also that there would be an additional effect of posture on ventilation heterogeneity within the lungs.…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, these results suggest that elevated MBW indices induced by airway constrictions are more variable in general, which is observed experimentally in CF and asthma patients through the increased sensitivity of LCI to posture [36,37], as well increased inter-patient variability [38].…”
Section: Discussionmentioning
confidence: 56%
“…More broadly, these results suggest that elevated MBW indices induced by airway constrictions are more variable in general, which is observed experimentally through the increased variance in LCI measured in CF and asthma patients [46], as well as an increased sensitivity of LCI to posture which affects the distribution of ventilation due to gravity [47,48]. This latter affect can be understood by perturbing acinar elastance, which affects their rate of ventilation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation